2016
DOI: 10.1080/19406940.2016.1170716
|View full text |Cite
|
Sign up to set email alerts
|

Anti-doping and legitimacy: an international survey of elite athletes’ perceptions

Abstract: Anti-doping and legitimacy: an international survey of elite athletes' perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 44 publications
2
38
0
Order By: Relevance
“…It has also been shown that elite athletes have doubts about the global equivalence of the anti-doping work (e.g. de Hon et al, 2011;Overbye & Wagner, 2013) and that this distrust could constitute a threat to the legitimacy of the work as a whole (Efverström et al, 2016). Procedural justice, with perceived fair actions, is an important component of the legitimacy of a social order (Tyler, 2006, Tyler & Jackson 2014, such as anti-doping.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that elite athletes have doubts about the global equivalence of the anti-doping work (e.g. de Hon et al, 2011;Overbye & Wagner, 2013) and that this distrust could constitute a threat to the legitimacy of the work as a whole (Efverström et al, 2016). Procedural justice, with perceived fair actions, is an important component of the legitimacy of a social order (Tyler, 2006, Tyler & Jackson 2014, such as anti-doping.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This was emphasized as having a negative effect on the legitimacy of anti-doping work. Additionally, a quantitative international study showed that athletes question the equity of the worldwide implementation of several anti-doping elements, which was considered to put the legitimacy of anti-doping work at risk (Efverström et al, 2016).…”
Section: Anti-doping At the Individual Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Elite athletes' opinions on and possible reactions to legalising 'doping' (or specific drugs like AAS and EPO) under medical supervision are important, especially considering that elite athletes are i) those who would be most affected, and ii) the main stakeholders when considering the legitimacy of anti-doping rules (Efverström et al, 2016;Overbye, 2016). Moreover, as pointed out by Møller (2010), one argument that both supporters and opponents of doping legalisation seem to agree on is that the interests of athletes should carry considerable weight.…”
Section: A Critical Appraisal Of the Zero-tolerance Approach And The mentioning
confidence: 99%
“…Furthermore, the paradoxes and unintended effects of anti-doping measures have attracted more attention in recent years. The paradoxes relate to how the comprehensive set of rules developed to protect athletes' health and secure equality and fairness in sport have created new forms of inequalities between athletes subjected to different anti-doping regimes (Efverström et al, 2016;Hanstad, Skille & Loland, 2010;Waddington, 2010;Overbye & Wagner, 2014;Overbye, 2016) and situations which may have negative effects on some athletes' health (Bourdon, Schoch, Broers & Kayser, 2015;Overbye & Wagner, 2013;Lentillon-Kaestner, 2013). Other issues of concern relate to: the collateral damage of excessive rule enforcement, e.g.…”
Section: Introductionmentioning
confidence: 99%